Numerical study on heat transfer of turbulent channel flow over periodic grooves - Eiamsa-ard, Smith; Promvonge, Pongjet (My University, 2008)
A numerical investigation of turbulent forced convection in a two-dimensional channel with periodic transverse grooves on the lower channel wall is conducted. The lower wall is subjected to a uniform heat flux condition while the upper wall is insulated. To investigate turbulence model effects, computations based on a finite volume method, are carried out by utilizing four turbulence models: the standard k - ε, the Renormalized Group (RNG) k - ε, the standard k - ω, and the shear stress transport (SST) k - ω turbulence models. Parametric runs are made for Reynolds numbers ranging from 6000 to 18,000 with the groove-width to channel-height ratio (B/H) of 0.5 to 1.75 while the groove pitch ratio of 2 and the depth ratio of 0.5 are fixed throughout. The predicted results from using several turbulence models reveal that the RNG and the k - ε turbulence models generally provide better agreement with available measurements than others. Therefore, the k - ε model is selected to use in prediction of this complex flow. In addition, the results of the heat transfer coefficient, friction factor, skin friction coefficient and thermal enhancement factor are also examined. It is found that the grooved channel provides a considerable increase in heat transfer at about 158% over the smooth channel and a maximum gain of 1.33 on thermal performance factor is obtained for the case of B/H = 0.75. This indicates that the reverse/re-circulation flow in a channel with transverse grooves can improve the heat transfer rate. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Channel; Friction; Groove; Heat transfer; Thermal enhancement; Turbulent flow